Kurikulum dan Pendidikan: Kajian Konseptual Pembelajaran Science di Madrasah Ibtidaiyah Indonesia dan Sekolah Dasar Negara Maju - Ibad, Taqwa Nur; Oktori, Agus Riyan; Wahidah, Finadatul; Prasetyo, Sigit (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Curriculum is the soul of education, to develop it as an effort for improvement and progress is a must and necessity for all educational institutions in Indonesia, especially those in Madrasah Ibtidaiyah (Islamic basic school). This research aims to examine the implementation of learning curriculum in Indonesia and in several developed countries which become a reference of innovation and answer to changes and challenges of the times. IPAS itself is an abbreviation of IPA (natural science) and IPS (social science) which is a new term designed by the government in the content of the current Merdeka Curriculum. In terms of content, IPAS is very close to nature and human interaction. Its learning needs to present a context that is relevant to the natural and environmental conditions around students. The research method used was a qualitative research method with a library research approach. Students’ need based learning is one of the author's findings in investigating science (IPAS) learning in the Merdeka Curriculum. Apart from that, today's digital era is an extraordinary challenge for an educator to be able to explore fun learning